2014
DOI: 10.1515/ijamh-2013-0331
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of health behaviors and their associated factors among a sample of university students in India

Abstract: Students had a high proportion of health behavior practices. Several high health risk practices were identified, including overweight, poor dental practices, poor dietary and sleeping habits. It is hoped that the gender-specific predictors identified, including sociodemographics as well as social and mental health variables, can also be utilized in designing health promotion programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 44 publications
(79 reference statements)
1
8
0
Order By: Relevance
“…The results of a research conducted in Kuwait for assessing the health promoting style of nursing students showed that males achieved higher scores compared to females (3). Emami et al and Plutzer et al reported a significant difference between gender and health promoting behaviors (21,28), which was consistent with the present study. They aimed at examining health behaviors.…”
Section: Discussionsupporting
confidence: 93%
“…The results of a research conducted in Kuwait for assessing the health promoting style of nursing students showed that males achieved higher scores compared to females (3). Emami et al and Plutzer et al reported a significant difference between gender and health promoting behaviors (21,28), which was consistent with the present study. They aimed at examining health behaviors.…”
Section: Discussionsupporting
confidence: 93%
“…Likewise, a healthy diet is understood to play a significant role in the lives of university students—that is, a considerably large population group which could be targeted to prevent numerous health problems [ 6 ]. Indeed, international research has demonstrated that student life in the university setting is characterized by many changes in eating behaviors and dietary patterns [ 7 ; 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 23 , 24 ] One cross-sectional survey of 800 university students in India found that there was a high rate of overweight and obesity and poor dietary patterns. [ 25 ] With the development of technology, more and more college students are using electronic devices. Researchers have begun to pay increased attention to the impact of electronic equipment on the health of students.…”
Section: Introductionmentioning
confidence: 99%